2009
DOI: 10.1016/j.ejcts.2008.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Presence of coronary collaterals is associated with a decreased incidence of cognitive decline after coronary artery bypass surgery☆

Abstract: In patients undergoing first-time coronary artery bypass grafting, presence of coronary collaterals is associated with a decreased risk of cognitive decline at both 3 and 12 months of follow-up. This trend persists at 5-year follow-up. Preoperative differences in the cardiac vascular condition may therefore predict cognitive outcome in patients undergoing coronary artery bypass grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…Of the 14 studies, 13 had prospective observational designs; 1 randomized controlled trial compared cognitive outcomes between on‐pump and off‐pump coronary artery bypass grafting and analyzed their data with adjustment for surgery type . A single investigation was on glycemic control in a sample of 124 patients with diabetes; all other studies investigated POCD according to diabetes status and enrolled a total of N = 2990 patients of which N = 2518 were retained for follow‐up (see Table ). Publication dates spanned 2001 to 2015, and studies stemmed from countries in Europe, Asia, North America, and Australia.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 14 studies, 13 had prospective observational designs; 1 randomized controlled trial compared cognitive outcomes between on‐pump and off‐pump coronary artery bypass grafting and analyzed their data with adjustment for surgery type . A single investigation was on glycemic control in a sample of 124 patients with diabetes; all other studies investigated POCD according to diabetes status and enrolled a total of N = 2990 patients of which N = 2518 were retained for follow‐up (see Table ). Publication dates spanned 2001 to 2015, and studies stemmed from countries in Europe, Asia, North America, and Australia.…”
Section: Resultsmentioning
confidence: 99%
“…Well-developed collaterals can supply sufficient perfusion without leading to any symptoms, although lack of collaterals can cause fatal ischaemia and subsequent infarction. Previous reports demonstrated that the degree of coronary collateral perfusion itself could influence clinical outcomes in patients with coronary artery stenosis [13,14]. Therefore, the degree of coronary collateral development should be precisely evaluated to establish optimal treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the degree of coronary collateral development should be precisely evaluated to establish optimal treatment strategies. The Rentrop grade is a well-established means of scoring the degree of development of coronary collaterals according to the extent of contrast medium in the territory distal to CTO and has recently been applied in various studies [2,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Advancing age and education level appear to be the most important predictors identified, as older patients and those with lower educational levels can be prioritized when developing and trialling interventions to improve cognitive function. While advancing age has emerged as the most common predictor of cognitive outcome, 25,28,30,33,36,[40][41][42][43]46,48,50,54,56,57 this was reported inconsistently. Those that found age to be non-predictive of cognitive outcome tended to have smaller sample sizes.…”
Section: Discussionmentioning
confidence: 99%